Contrast‐Enhanced Ultrasound Features of Adult Xp11.2 Translocation Renal Cell Carcinoma: Differential Diagnosis With Three Main Renal Cell Carcinoma Subtypes. (1st February 2022) - Ma, Wenliang; Zhang, Fan; Huang, Haifeng; Wang, Wei; Zhu, Yiqi; Lu, Yanwen; Guo, Hongqian; Gan, Weidong
Abstract : Objectives: To investigate the sonographic features in Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) using both conventional ultrasound (US) and contrast‐enhanced US (CEUS) and evaluate the usefulness of sonographic imaging characteristics to differentiate between Xp11.2 tRCC and the three common RCC subtypes. Methods: Thirty‐four adult Xp11.2 tRCC patients who preoperatively underwent both conventional US and CEUS and had solitary renal lesions and pathological confirmation after surgery were enrolled. Control matched patients included 131 with clear cell RCC (ccRCC), 48 with papillary RCC (pRCC), and 35 with chromophobe RCC (chRCC). Conventional US and CEUS data of all patients were retrospectively analyzed and compared. Results: Xp11.2 tRCC was more common in young women. The echogenicity of Xp11.2 tRCC lesions was hypo‐ and isoechoic relative to the adjacent renal cortex. A higher frequency of calcification within tumors was detected in Xp11.2 tRCC, but the presence of color flow signal (26.5%, 9/34) was much lower. Regarding CEUS features relative to the adjacent renal cortex, synchronous wash‐in (61.8%, 21/34), iso‐enhancement at peak (55.9%, 19/34), and fast wash‐out (50.0%, 17/34) were more common in Xp11.2 tRCC. Moreover, an integrated variables model based on these features could differentiate Xp11.2 tRCC from ccRCC, pRCC, and chRCC (area under the curve, sensitivity, and specificity: 0.934, 92.0%, and 86.0%; 0.907, 88.0%, and 87.0%; and 0.808, 65.0%, and 99.0%, respectively). Conclusions: Combining conventional US and CEUS lesion features with clinical information may provide a feasible and effective method to differentiate Xp11.2 tRCC from ccRCC, pRCC, and chRCC.